2016
DOI: 10.1177/1351010x16637527
|View full text |Cite
|
Sign up to set email alerts
|

A simplified model to evaluate noise reduction interventions in the urban environment

Abstract: Traffic noise is a major problem in all large cities. The surface acoustical characteristics (e.g. referred to roads, pedestrian traffic areas, building façades, building surfaces, in general) affect the noise propagation in the urban environment. Through a better outdoor design and management (e.g. by means of green areas, porous asphalt, speed control), or building refurbishment actions (acoustic plaster, absorbing shading devices), the increasing of surface absorption could be useful to mitigate noise envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The results indicate that changing to grass surface does not provide large further reduction compared to increasing facade absorption. A similar result is obtained by Magrini and Lisot [46] , who have investigated the influence of absorbent paving and green areas within street canyons instead of existing road and sidewalk areas. The design changes were not found to affect noise levels near the facade significantly.…”
Section: Groundsupporting
confidence: 82%
“…The results indicate that changing to grass surface does not provide large further reduction compared to increasing facade absorption. A similar result is obtained by Magrini and Lisot [46] , who have investigated the influence of absorbent paving and green areas within street canyons instead of existing road and sidewalk areas. The design changes were not found to affect noise levels near the facade significantly.…”
Section: Groundsupporting
confidence: 82%
“…Plastering of outer walls to decrease sound reflections in noisy, densely populated areas (e.g. near airport areas 8 and urban canyons 22 );…”
Section: Experimental Campaignmentioning
confidence: 99%
“…Magrini and Lisot [ 49 ] examined the various traffic and building-related attributes and whether they had impacts on noise propagation or not. As such, the authors performed a model for understanding building facade effects (absorption and green materials) as well as geometries (road factors, building heights, balconies), and found that simpler building shapes and narrower road typologies tend to reduce noise propagation.…”
Section: Building Material/shape/geometrymentioning
confidence: 99%